Analysis on quality improvement of used cooking oil with young pineapple (Ananas comosus) using Taguchi Method. Issue 1 (November 2020) - Arfan, Muhammad; Supartono, Wahyu; Yuliando, Henry
Abstract: Cristal small industry is one of the industries which focuses on processing the snake fruit chips in Sleman, Yogyakarta. To purify used cooking oil in this industry is using young pineapple as adsorbent. However, the industry did not know optimal condition of its adsorbent during the purification process. This research is aimed to determine the combination of optimum factor level of control factors that affect the quality of used cooking oil. Four control factors are as follow; processing time, temperature, atmospheric pressure and thickness of pineapple slice. The number of levels of each factor is three level. Based on the number and factor level used, the experimental design was prepared based on the orthogonal matrix L9 (34) as a tool in Taguchi method. Data analysis are conducted by using signal to noise ratio (SNR), factor effect, variance analysis, multiple performance characteristic and confirmation test. The results showed that the optimal condition for using young pineapple as adsorbent in used oil purification were temperature of cooking at 88°C, processing time for 70 minutes, atmospheric pressure of 72 mmHg and pineapple thickness of 4 mm.